Predicting nitrogen availability for rice (Oryza sativa) through carbon-nitrogen relationship under Himalayan acidic soils of north-eastern India - Laxminarayana, K (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2003-05 to study the potentially mineralizable N and distribution of inorganic N fractions in some of the rice (Oryza sativa L.) soils representing from 6 districts of Meghalaya to establish the relationship between organic carbon and N availability indices. The results shows that the organic carbon, mineral N and available N as extracted by alkaline KMnO4, acid KMnO4, and H2O2, oxidation were significantly correlated with all the plant growth parameters. Ammoniacal N was found to be the major contributing fraction to the oxidizable N by various chemical methods as evident from the step down regressions drawn between N availability indices and soil properties. Alkaline KMnO4, oxidizable N showed highly significant relationship with ammonical N which is the major contributing inorganic N fraction for crop nutrition as well as other biological indices and it can be adjudged as superior than other N availability indices with a critical limit of 320 kg/ha. It was observed that the organic carbon had highly significant relationship with N availability indices and inorganic N fractions with a critical limit of 1.65 % delineating high and low status of available N for rice soils. The regression equations for determining available N on the basis of organic carbon content indicated that the soils with 1.65 % organic carbon closer to the critical limits of other N availability indices. Thus the organic carbon content can be used for predicting available N in the fertilizer adjustments, if determined alone. The study also emphasized the need of refixing critical limits for organic carbon and available N in the soils of north-eastern Himalayan region, especially rice-growing soils of Meghalaya to enhance the N-use efficiency and rice productivity.